The Influence Of School Principals’ Managerial Skills And Teacher’s Work Motivation On The Quality Of Junior High School - Afiah, Dian Nur; rasiman; Sumarno (AJIS: Academic Journal of Islamic Studies, 2025)
This study investigates the influence of school principals' managerial skills and teachers' work motivation on the quality of Junior High Schools in Kedungwuni District, Pekalongan Regency. The research used a quantitative approach with a descriptive design involving 110 teachers from various schools in the district. Data was collected using questionnaires with a Likert scale and performed using multiple regression analysis. The findings indicate that school principals' managerial skills and teachers' work motivation significantly influence school quality. The results showed that school principals' managerial skills contributed 61.7% to improving school quality, while teachers' work motivation contributed 72.0%. Moreover, both variables accounted for 63.8% of the variation in school quality, indicating that they work together to enhance educational outcomes. The study further identified that the most significant dimension of managerial skills was human relations, followed by conceptual and technical skills. At the same time, intrinsic motivation played a more prominent role in motivating teachers than extrinsic motivation. Based on these findings, it is recommended that school principals enhance their managerial skills, especially in technical aspects, and that teachers actively improve their motivation. The local education authority should also support the development of school principals' leadership capabilities and create programs that foster teachers' professional growth. This study contributes to understanding how effective leadership and motivated teachers can significantly improve school quality, offering valuable insights for educational policymakers and practitioners.